THE INDONESIAN ISLAM: LAW AND THE IDEOLOGICAL PERSPECTIVE. - Syukur, Iskandar; Yurni Ahmad, Noor Sulastry (al-'adalah, 2014)
Abstract: The Indonesian Islam: Law and the Ideological Perspective. This article is aimed at exploring the development of Islam in Indonesia with particular references to the ideological perspective and its impact on Islamic law. At the beginning of the twentieth century, there were two ideologies in Indonesian Muslims. The first ideology believes that the consistence with traditions is very important while the other believes that Islamic teachings are able to change according to time and place. Although having difference in orientation, both ideologies devoted themselves to social, religious and political activities. In political sphere, however, both ideologies, were faced with secular nationalist ideology. Such a competition ended with a failure that made Indonesian Muslims receding into the background. After realizing of the failure in politics, both ideologies turn their orientation to cultural Islam. Through this orientation, peaceful and mutual understanding between Muslims and state began to grow. Subsequently, the government, especially New Order regime, identified itself with the religious activities and opened a chance to promote Islamic values. It was from such a relationship that the Islamic law gradually developed in Indonesia. Abstrak: Islam Indonesia: Perspektif Ideologis dan Hukum. Artikel ini bertujuan untuk mengungkap perkembangan Islam di Indonesia dengan titik berat pada aspek ideologis dan pengaruhnya pada hukum Islam. Seperti dimaklumi, sejak awal abad ke-dua puluh, ada dua bentuk ideologi yang hidup di kalangan umat Islam Indonesia; Ideologi pertama percaya bahwa konsistensi dengan tradisi sangatlah penting sementara ideologi yang lain percaya bahwa ajaran Islam dapat berubah sesuai dengan tempat dan waktu. Meski berbeda orientasi, kedua ideologi tersebut sebenarnya sama-sama memiliki kepedulian terhadap dunia politik. Di dunia politik, kedua ideologi itu, dengan karakternya masing-masing, kemudian berhadapan dengan ideologi nasionalis sekuler. Kompetisi itu yang kemudian berujung kepada kegagalan dan membuat perkembangan umat Islam di Indonesia surut ke belakang. Setelah gagal dalam bidang politik, kedua ideologi tersebut mengubah orientasi mereka menjadi Islam kultural. Melalui orientasi ini, sikap saling memahami mulai terbangun antara antara umat Islam dan pemerintah. Bahkan, pada tahapan berikutnya, pemerintah, khususnya rezim Orde Baru, mengidentifikasikan dirinya dengan kegiatan keagamaan dan memberikan kesempatan untuk mempromosikan nilai-nilai Islam. Lewat hubungan yang demikian itulah hukum Islam di Indonesia secara berangsur-angsur berkembang.